Clinical implications of pathologic factors after thyroid lobectomy in patients with papillary thyroid carcinoma. (December 2017) - Park, Young Min; Lee, Doh Young; Oh, Kyung Ho; Cho, Jae-Gu; Baek, Seung-Kuk; Kwon, Soon-Young; Jung, Kwang-Yoon; Woo, Jeong-Soo
Highlights: micro-ETE was an important prognostic factor associated with RFS. The 10-year RFS was 99.2% for patients without ETE. The 10-year RFS was 92.2% for patients with micro-ETE. Appropriate US follow-up should be required in patients with the risk factors. Abstract: Objective: We evaluated the clinical and prognostic significance of pathologic factors by analyzing the treatment results of patients who underwent thyroid lobectomy. Materials and methods: We retrospectively analyzed data from 734 patients diagnosed with papillary thyroid cancer who underwent thyroid lobectomy at Korea University Hospital from January 2004 to December 2016. Results: A total of 734 patients were included in the study and their mean age was 44.5 years (range, 15–83). On univariate analysis, tumor size and recurrence-free survival were significantly related. The 10-year recurrence-free survival was 98.3% for tumors ≤1 cm, 77.8% for >1 cm and ≤2 cm, and 66.7% for >2 cm (p = 0.014). Recurrence-free survival was significantly different between patients with and without microscopic extrathyroidal extension (p = 0.002). The 10-year recurrence-free survival rate was 99.2% for patients without extrathyroidal extension and 92.2% for patients with microscopic extrathyroidal extension. Multivariate analysis showed only microscopic extrathyroidal extension was significantly correlated with recurrence-free survival (p = 0.029). Conclusion: In patients undergoing thyroid lobectomy for low-risk papillary thyroid cancer, microscopic extrathyroidal extension was an important prognostic factor associated with recurrence-free survival. However, in cases with microscopic extrathyroidal extension findings on postoperative pathologic examination, appropriate ultrasonographic follow-up of the contralateral thyroid lobe and cervical lymph node to facilitate early detection and prompt treatment of recurrence can control the disease without a deterioration of survival rate.